Cryptocurrencies — Virtual Gold - Kudłacik, Przemysław; Sikora, Agnieszka (No Limits, 2023)
Cryptocurrency is a term not coincidentally made up of two elements: the prefix crypto- and the noun currency. It is basically a means of settlement, not stored, however, in the computer system of any bank, but rather maintained by thousands of computers scattered around the world. It is built on a technology called blockchain. How are cryptocurrencies created? Can something that does not physically exist have value? It is still difficult to say if cryptocurrencies have more advantages or disadvantages.